2010
DOI: 10.1007/s12010-010-9025-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Shear Modeled Microgravity on the Characterization of Recombinant β-D-Glucuronidase Expressed in Pichia pastoris

Abstract: In this study, we used a high-aspect-ratio vessel (HARV), which could model environment of microgravity on ground to investigate for the first time the effects of low-shear modeled microgravity (LSMMG) on the characterization of recombinant β-D-glucuronidase expressed in Pichia pastoris. The β-D-glucuronidase gene (GenBank accession no. EU095019) derived from Penicillium purpurogenum Li-3 encoding β-D-glucuronidase (PGUS) was expressed in P. pastoris GS115 in two different environments of LSMMG and normal grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…26 In this study, the reason for enhancement of PGUS expression may be related to genes transcription. A significant number of yeast genes were found to be up-or downregulated by more than one to seven-fold as a result of growth under LSMMG analyzed using the DNA microarray method.…”
mentioning
confidence: 84%
“…26 In this study, the reason for enhancement of PGUS expression may be related to genes transcription. A significant number of yeast genes were found to be up-or downregulated by more than one to seven-fold as a result of growth under LSMMG analyzed using the DNA microarray method.…”
mentioning
confidence: 84%
“…These results suggested that microgravity effects could be used for efficient production of recombinant proteins from engineered microorganisms. Interestingly, the enzyme catalysis process was also changed under microgravity [25][26][27]. The activities of intracellular antioxidant enzymes, superoxide dismutase and catalase, were higher under space microgravity condition [25].…”
Section: Tuning Recombinant Protein Expression By Microgravitymentioning
confidence: 99%
“…The activities of intracellular antioxidant enzymes, superoxide dismutase and catalase, were higher under space microgravity condition [25]. Qi et al revealed the significant alterations in catalytic properties of the recombinant β-glucuronidase in response to low-shear modeled microgravity effect [27]. The catalytic efficiency (kcat/Km) of this enzyme expressed by E. coli was 3.7 times higher under microgravity than under which of normal gravity ( Table 1).…”
Section: Tuning Recombinant Protein Expression By Microgravitymentioning
confidence: 99%
“…Spaceflight has been reported to affect microbial cellular processes, such as cell growth [1], gene expression [2], and so on, therefore potentially producing unexpected (and possibly dangerous) changes in the natural biota within the space craft. For earth based organisms, microgravity is a key factor of the space condition, since all earth based organisms have been evolving under a 1g field for millions of years.…”
Section: Introductionmentioning
confidence: 99%